If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(1-x)+3x=-2x(x+1)
We move all terms to the left:
4(1-x)+3x-(-2x(x+1))=0
We add all the numbers together, and all the variables
4(-1x+1)+3x-(-2x(x+1))=0
We add all the numbers together, and all the variables
3x+4(-1x+1)-(-2x(x+1))=0
We multiply parentheses
3x-4x-(-2x(x+1))+4=0
We calculate terms in parentheses: -(-2x(x+1)), so:We add all the numbers together, and all the variables
-2x(x+1)
We multiply parentheses
-2x^2-2x
Back to the equation:
-(-2x^2-2x)
-(-2x^2-2x)-1x+4=0
We get rid of parentheses
2x^2+2x-1x+4=0
We add all the numbers together, and all the variables
2x^2+x+4=0
a = 2; b = 1; c = +4;
Δ = b2-4ac
Δ = 12-4·2·4
Δ = -31
Delta is less than zero, so there is no solution for the equation
| x^2+3x=(-2) | | 8u-3u=45 | | 2/15c=8.8 | | −6(3p−1)=−120 | | 2x=100=180 | | b2=-1 | | 26=3t+2 | | (-19x)+6x-(-18x)-(-1)=(-19) | | (3y-10)°=50 | | k+1=2 | | 38=8u-2u | | 6+10x=-2(-4x-6) | | x+23.45=36.80 | | -7(x-19)=-84 | | 13y+y-8y-5y+3y=12 | | 7x=20-4x | | 8.25+x=23 | | 8.2+x=23 | | 8x=19=180 | | 3-5(-3n+5)=0 | | -8n+32=8(5n+4) | | -3(x+2)+5-4x=-36 | | (-3,7y+11=4y+11) | | x+8=37.5 | | 3x-2=-2+12 | | -8n+32=40n+32 | | 3x+4x-25=-4 | | 5x-2(x-5)=-2+5x-4 | | 5-2x=0.25x | | s/7+8=3 | | 6x-5.5=42 | | 19d-(-17d)+(-16d)-d-(-11)=(-8) |